Who Uses Buddhist Coping? Convergent and Discriminant Validity for the BCOPE - Iii, Russell E. Phillips (Research in the social scientific study of religion, 2015)
In the past two decades, researchers have often examined the construct of religious coping, including its predictors and implications. However, few such studies are conducted on Buddhists. Researchers recently created a reliable and valid scale of Buddhist coping (the bcope), and correlated the scale with measures of adjustment to stress, but no research has yet explored predictors of Buddhist coping. The present study examined how various demographic and spiritual variables related to 14 Buddhist coping methods in a sample of 860 Buddhists living in the United States. Compared to less spiritual individuals, spiritual persons generally employed more Buddhist coping methods with positive implications, but not Buddhist coping techniques associated with negative implications. Older, more experienced Buddhists were typically less likely to use negative Buddhist coping methods than younger Buddhists. There were few differences in Buddhist coping across Buddhist sects, gender, or ethnicity. The present study provides information on the convergent and discriminant validity of the bcope, and who is likely to employ various Buddhist coping methods. Practical implications and future research directions are discussed.